Logarithm and square root definite integral

Calculus Level 5

Let A = 0 ( e 1 ) 2 4 e ln ( x + 1 + x ) d x A = \int_{0}^{\frac{(e-1)^2}{4e}} \ln ( \sqrt{x+1} + \sqrt{x} ) dx Input e A eA as your answer.


The answer is 0.25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jul 29, 2018

First note that ( e 1 ) 2 4 e = sinh 2 1 2 \tfrac{(e-1)^2}{4e} = \sinh^2\tfrac12 . With the substitution x = sinh 2 u x = \sinh^2u , we have A = 0 1 2 ln ( cosh u + sinh u ) × 2 sinh u cosh u d u = 0 1 2 u sinh 2 u d u = 1 4 0 1 v sinh v d v = 1 4 ( [ v cosh v ] 0 1 0 1 cosh v d v ) = 1 4 [ v cosh v sinh v ] 0 1 = 1 4 ( cosh 1 sinh 1 ) = 1 4 e \begin{aligned} A & = \; \int_0^{\frac12} \ln(\cosh u + \sinh u) \times 2\sinh u \cosh u\,du \; = \; \int_0^{\frac12} u\sinh 2u\,du \; = \; \tfrac14\int_0^1 v \sinh v\,dv \\ & = \; \frac14\left(\Big[v\cosh v\Big]_0^1 - \int_0^1 \cosh v\,dv \right) \;= \; \frac14\Big[v \cosh v - \sinh v \Big]_0^1 \; = \; \tfrac14(\cosh 1 - \sinh 1) \\ & = \; \tfrac{1}{4e} \end{aligned} so that e A = 1 4 eA = \boxed{\tfrac14} .

@Mark Hennings Amazing approach Sir!!!!!!!

Aaghaz Mahajan - 2 years, 10 months ago

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...